Impact of multidomain preventive strategies on functional brain connectivity in older adults with cognitive complaint: Subset from the Montpellier center of the ancillary MAPT-MRI study - Perus, Lisa; Mangin, Jean-François; Deverdun, Jérémy; Gutierrez, Laure-Anne; Gourieux, Emmanuelle; Fischer, Clara; Van Dokkum, Liesjet E. H.; Manesco, Clara; Busto, Germain; Guyonnet, Sophie; Vellas, Bruno; Gabelle, Audrey; et al. (Frontiers in Aging Neuroscience, 2023)
The impact of multi-domain preventive interventions on older adults and, in particular on those with higher risk to develop Alzheimer’s disease (AD), could be beneficial, as it may delay brain cognitive decline. However, the precise mechanism of such positive impact is not fully understood and may involve brain reserve and adaptability of brain functional connectivity (FC) adaptability. To determine the effect of multidomain interventions (involving physical activity, cognitive training, nutritional counseling alone or in combination with omega-3 fatty acid supplementation and versus a placebo) on the brain, longitudinal FC changes were assessed after 36 months of intervention in on 100 older adults >(above 70 years’ year-old) and with subjective cognitive complaints. No global change in FC was detected after uni or multidomain preventive interventions. However, an effect of omega-3 fatty acid supplementation dependent on cognitive decline status was underlined for frontoparietal, salience, visual and sensorimotor networks FC. These findings were independent of the cortical thickness and vascular burden. These results emphasize the importance of patient stratification, based on risk factors, preventive interventions.